FACTORS THAT DETERMINE THE CREDIT-LENDING FEASIBILITY ON KOPAAS HIPPATAS - Didin Mukodim; Ari Setiawan (Universitas Gunadarma, 2009)
Banking and non-banking financial institutions entrench within their credit-lending policy the feasibility standards for their debtor candidates. Standards and procedures are established to avoid upcoming problematic credits, for example happened when a debtor is unable to pay the credit. The objective of this research is to identify factors that affect debtor’s feasibility in getting a loan/credit. For its study focus, this research uses Kopaas Hippatas a cooperative in Tasikmalaya. The influential factors are acquired using discriminant analysis. Discriminant analysis enables the authors to clearly identify the differences and to classify debtor candidates into potential non-problematic and problematic in the term of paying the loan. The analysis corroborates four factors in determining credit lending of Kopaas Hippatas, i.e. credit amount, debtor age, number of dependant and settled installments; also affirmed in this study are two predictors, i.e. number of dependant and proposed credit amount. Credit amount is confirmed as the most dominant and significant factor in categorizing the debtor behavior in term of paying the credit.Keywords: credit lending, postponed debtor, budget and installment